Comparative Analysis Of Transportation Infrastructure Development Through PPP Scheme In Indonesia And Japan - Maimunah, Siti (Warta Penelitian Perhubungan, 2012)
During the last decade, infrastructure development has become the main focus for several developing countries seeking to achieve a high economic gr()'l,()th rate. H()'l,()ever, developing sufficient infrastructure to meet the demand side is quite challenging, especially given the financing required. To fulfill this condition, methodology for financing schemes for infrastructure projects with Public Private Partnerships (PPP) has recently been significantly increased in both developed and developing countries. To attract private investments, the government has attempted to improve the legal and regulatory framework at transportation sector. H()'l,()ever, revising the infrastructure laws is not enough to attract private sector investment. The government of Indonesia still needs more efforts to create an attractive investment climate. Although Indonesia has had a system for PPP methodology, only a few projects have been implemented. The objectives of this study are to learn about and understand Japan's PFI methodology, particularly type I, and find the benefits of its implementation in terms of the development of public infrastructures and it can be implemented in Indonesia. Through comparative analysis between PFI methodology in Japan and PPP methodology in Indonesia, it can be concluded that in general, since the project scope between Japan's PFI and Indonesia's PPP are fundamentally different, not all procedures in Japan's PFI methodology can be applied to improve Indonesia's PPP methodology. To apply some lessons learned from Japan's PFI, it is necessary to consider the nature and culture of the country. Based on the current condition of PPP projects in Indonesia, the government needs to take specific actions, including: institutional framework, service payment scheme and risk allocation.Keywords: Japan's PFI, Indonesia's PPP, Comparative Analysis Selama dekade terakhir, pembangunan infrastruktur telah menjadi fokus utama bagi beberapa negara berkembang untuk mencapai tingkat pertumbuhan ekonomi yang tinggi. Namun, mengembangkan infrastruktur untuk memenuhi permintaan cukup menantang, terutama mengingat pembiayaan yang diperlukan. Untuk memenuhi kondisi ini, maka dikembangkan metodologi pembiayaan yang dikenal dengan Kerjasama Pemerintah Swasta (KPS), yang akhir-akhir ini telah meningkat secara signifikan di banyak negara maju dan berkembang. Untuk menarik investor, pemerintah telah berusaha untuk memperbaiki kerangka hukum dan peraturan di sektor transportasi. Namun, merevisi undang-undang infrastruktur tidak cukup untuk menarik investor. Pemerintah Indonesia masih membutuhkan lebih banyak upaya untuk menciptakan iklim investasi yang menarik. Meskipun Indonesia telah memiliki sistem untuk metodologi KPS, hanya beberapa proyek telah dilaksanakan. Tujuan dari penelitian ini adalah untuk mempelajari dan memahami metodologi PFI di Jepang, terutama tipe I, dan menemukan manfaat dari pelaksanaannya dalam hal pembangunan infrastruktur umum dan dapat diterapkan di Indonesia. Melalui analisis komparatif antara metodologi PFI di Jepang dan PPP metodologi di Indonesia, dapat disimpulkan bahwa secara umum, karena ruang lingkup proyek antara PFI di Jepang dan di KPS di Indonesia pada dasamya berbeda, tidak semua prosedur dalam metodologi PFI di Jepang dapat diterapkan untuk meningkatkan PPP di Indonesia. Berdasarkan hasil analisis PFI di Jepang, maka perlu mempertimbangkan sfat dan budaya negara. Berdasarkan kondisi saat ini, maka pemerintah perlu mengambil tindakan tertentu untuk proyek KPS di Indonesia, termasuk: kerangka kelembagaan, skema layanan pembayaran dan alokasi risiko.Kata kunci: PFI di Jepang PF!, KPS di Indonesia, Analisis Perbandingan